Fostering flow experiences at work: a framework and research agenda for developing flow interventions - Bartholomeyczik, Karen; Knierim, Michael T.; Weinhardt, Christof (Frontiers in Psychology, 2023)
Flow, the holistic experience of intrinsic motivation and effortless attention, is positively associated with job performance, work engagement, and well-being. As many individuals struggle to enter and maintain flow states, interventions that foster flow at work represent valuable catalysts for organizational and individual improvement. Since the literature on work-related flow interventions is still sparse, this article aims to provide a foundation for the systematic development of these interventions. Through a narrative review of the empirical and theoretical field, we develop a comprehensive framework with three dimensions, (1) the intervention aim (entering, boosting, or maintaining flow), (2) the target (context, individual, or group), and (3) the executor (top-down or bottom-up), for systematically classifying flow interventions at work. We complement the framework with guiding questions and concrete starting points for designing novel interventions. In addition, we explain how to build on these dimensions when operationalizing flow as the outcome variable in evaluating intervention effectiveness. By acknowledging individual and situational variability in flow states and the contingent limitations of flow interventions, we offer a broad perspective on the potential for fostering flow at work by using adaptive interventions.